Estudo da perda de ductilidade a quente e resistência à corrosão de vergalhões laminados com e sem a utilização da etapa de reaquecimento - Rocha Filho, Francisco Alberto Marreiros da (2017)
Hot rolling is one of the main forming processes where the semi-finished product obtained in the steel plant, is deformed plastically by compression forces applied between rotating cylinders. During rolling process the hot shortness phenomenon may occur and this may cause of split ends of bar during the sequence of cross section reduction passes. This split ends of bar can be severe and cause disruptions in the production process. The hot shortness may be associated with several factors, such as: the chemical composition of steel; the defects present in the semi-finished product, in the case of billet, produced in the process of continuous casting; the steel temperature during the process; and the conditions of rolling process, where it is worth mentioning the deformation rates, reductions, cylinder diameters, type of rolling stand and pass design. In the process under study, hot shortness generally occurs associated with the production of low carbon steel bars which are rolled from billets with as cast structure, which do not go through the reheating process in natural gas furnaces. Since there is great difficulty in inspecting semi-finished products directly from the continuous casting process, and there are limitations related to modification of rolling process conditions, the objective is to evaluate the influence of billet temperature along its section and the microstructure formed prior to the rolling process, mainly related to grain size and the presence of sulphides. These factors were associated with the hot shotness phenomenon of the steel, through a comparative examination between steels rolled directly from continuous casting and steels that pass through the reheating furnace before being rolled. It was possible to observe that the directly rolled billets had a smaller grain size prior to rolling and higher temperature loss throughout the process, which factors associated with a low Mn / S ratio and high reductions and deformation rates favored the hot shortness of bar during the rolling process. Both production routes provide small microstructural differences in the final product, which did not cause significant differences in the properties of corrosion resistance and mechanical properties of rebar.